"UZBEK BOWED STRING INSTRUMENTS: HISTORY, THEORY AND PRACTICE (The traditional and contemporary kobuz as an example)" (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
To highlight the theoretical, technological and performance capabilities of the Uzbek stringed musical instrument kobuz from the perspective of the development of national traditional art.